Students Perceptions of Physical Disabilities in Higher Education: A Case Study at Surabaya State University (UNESA) - Ramadhani, Jasmine Citra; Puspasari, Durinta (GRAB KIDS: Journal of Special Education Need, 2025)
This study aims to explore the perceptions of students at Surabaya State University particulary in the Office Administration Education toward individuals with physical disabilities. The research uses a descriptive qualititative approach through interviews, questionnaires, and documentation. The results show that the majority of students have positive perceptions, expressing equality in rights and potential for individuals with physical disabilities in education. However, there are still shortcomings in terms of campus infrastructure. The findings highlight the importance of improving facilities and inclusive education to create a disabilty – friendly educational environment.